Development and research of reflectance pulse oximeter; 12th International Conference on Actual Problems of Electronic Instrument Engineering (APEIE), October 2-4 , 2014, Novosibirsk - Martemjyanova N. I. Nina Ivanovna (2014, 2014)
Title screen